Post-inspection work after handing over process / Muhammad Azizul Haqim Ramli - Muhammad Azizul Haqim, Ramli (2017)
This report is essentially regarding the specific scope of work that had been done during the industrial training (1st of December 2016-1st April 2017). Industrial training is a great opportunity for students to learn about the industry, to establish important contacts and most importantly, to seed the beginnings for a career in your chosen profession. Students get out of industrial training what they are willing to invest in the process. With a positive attitude, industrial training can be a challenging and rewarding experience. The workplace that has been chosen to run the industrial training is Tenaga Nasional Berhad which is very well-known for its service in supplying electricity in our country, therefore there’s quite much of experience and vital information gathered during this 4-month industrial training here. The staff workers are amongst the professionals, diligently trained and splendidly experienced. Lots of industrial fields can be found here inspite supplying and generating electricity become their main scope of work here.